Bread making - improving quality - Cauvain, Stanley P. (Woodhead Publishing, 2011)
Edited by one of the world's leading authorities in the field, Bread Making: Improving Quality reviews key recent research on the ingredients determining bread characteristics. The text discusses what this information means for improved process control and a better, more consistent product.